2015
DOI: 10.22146/ijbiotech.7880
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Fermentation on Mixed Sugars Using Mixed Culture of Two Yeast Strains

Abstract: The objective of this study was to evaluate the use of mixed cultures of the recommended yeast strains from a previous study on ethanol fermentation using a substrate mixture consisting of sucrose, glucose, and fructose. There were three mixed (combination) cultures namely OUT7096/OUT7913, OUT7096/OUT7921, and OUT7913/OUT7921. The fermentation medium contained sugar mixture consisting of glucose, fructose, and sucrose with a composition generally close to the composition of sugars in sweet sorghum juice. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…In terms of the timeliness of switching between batches, perhaps the addition of fresh substrate occurs when the yeast growth has entered the death phase; thus, the available living cells are few. This assumption was based on a study reporting that the growth of S. cerevisiae in a medium with an initial sugar concentration of 10% entered the stationary phase at the 20 th hour (Jasman et al, 2013). Therefore, for a medium with a much lower sugar content, such as the coconut cream in the current study, both the stationary and subsequent death phases of S. cerevisiae cells will come earlier.…”
Section: Virgin Coconut Oil Qualitymentioning
confidence: 88%
“…In terms of the timeliness of switching between batches, perhaps the addition of fresh substrate occurs when the yeast growth has entered the death phase; thus, the available living cells are few. This assumption was based on a study reporting that the growth of S. cerevisiae in a medium with an initial sugar concentration of 10% entered the stationary phase at the 20 th hour (Jasman et al, 2013). Therefore, for a medium with a much lower sugar content, such as the coconut cream in the current study, both the stationary and subsequent death phases of S. cerevisiae cells will come earlier.…”
Section: Virgin Coconut Oil Qualitymentioning
confidence: 88%
“…In corroboration to these reports, Calabash pulp juice used as the substrate in this study is cheap and sourced from the environment where it does not compete with the food supply chain. Mixed cultures also have another characteristic of being able to ferment substrates containing several different sugars [27]. Ejelonu et al [12] reported that Calabash juice contains sugars such as sucrose, fructose and galactose.…”
Section: Discussionmentioning
confidence: 99%
“…Semakin lama waktu fermentasi, penurunan pH akan semakin tinggi sehingga rasa minuman yang dihasilkan akan semakin asam. Hal ini disebabkan khamir dan bakteri melakukan metabolisme terhadap sukrosa dan menghasilkan sejumlah asam-asam organik seperti asam asetat, asam glukoronat dan asam glukonat (Jasman et al, 2013). Peningkatan rasa asam ini sejalan dengan penelitian yang dilakukan oleh Nurhayati et al (2020) dimana semakin lama waktu fermentasi, maka rasa asam dari produk kombucha akan semakin tinggi dan rasa asamnya semakin kuat, sehingga kurang disukai oleh panelis.…”
Section: Tingkat Kesukaan Kombucha Teh Hitam Dengan Jenis Pemanis Dan...unclassified
“…Sedangkan untuk produk kombucha yang diproduksi selama 8 hari memiliki skala hedonic 4.6 yang menunjukkan panelis agak menyukai produk kombucha yang difermentasi selama 8 hari, sedangkan untuk yang diproduksi 12 hari mendapat skala hedonic 3.5 yang menunjukkan bahwa panelis cenderung agak tidak suka dengan aroma menyengat dari kombucha ini. Penurunan kesukaan panelis akibat lamanya waktu fermentasi diduga akibat proses fermentasi yang terus berjalan sehingga semakin banyak senyawa yang dihidrolisis dan semakin banyak asam organik seperti asam asetat, asam glukonat, dan asam glukoronat terbentuk (Jasman et al, 2013) sehingga aroma kombucha akan lebih masam. Menurut (Neffe-Skocińska, Sionek, Ścibisz, & Kołożyn-Krajewska (2017), aroma teh, lemon dan asam biasanya akan muncul pada produk kombucha.…”
Section: Tingkat Kesukaan Kombucha Teh Hitam Dengan Jenis Pemanis Dan...unclassified